Persepsi Santri Terhadap Pembiasaan Sholat Ashar Berjamaah Dan Dampaknya Terhadap Kedisiplinan: (Studi Di Madrasah Diniyah Miftahul Ulum Kejawan Tegowanu Grobogan) - Abdul Khanip; Ira Mutiaraningrum (Indonesian Journal of Islamic Education Studies (INJURIES), 2026)
This study is motivated by the importance of religious habituation in shaping students’ discipline, particularly through the practice of ashar congregational prayer. The aim of this research is to analyze students’ perceptions of the habituation of congregational prayer and its impact on discipline at Madrasah Diniyah Miftahul Ulum Kejawan Tegowanu Grobogan. This study employs a qualitative approach with a field research design. The research subjects include students (santri), teachers, and school administrators selected through purposive sampling. Data were collected through participatory observation, in-depth interviews, and documentation, and analyzed using the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing. The findings reveal that students’ perceptions of ashar congregational prayer habituation vary, including religious, normative, and formalistic perspectives. The implementation of congregational prayer is structured and continuous, consisting of preparation, implementation, and evaluation stages. This practice has a positive impact on students’ discipline, particularly in terms of time management, rule compliance, and behavior. However, the level of discipline varies due to internal and external factors. The study concludes that congregational prayer habituation is an effective strategy for fostering discipline, but its success largely depends on the process of value internalization through understanding and spiritual awareness.